The Common Market for Eastern and Southern Africas (COMESA) Free Trade Area (FTA) and Foreign Direct Investment (FDI) Nexus - Yahia, Yassin Elshain; Liu, Haiyun; Shah, Sayyed Sadaqat Hussain; Ali, Hisham Mohamed Hassan; Sultanuzzaman, Md Reza (Journal of Asian Business Strategy, 2019)
There is neither theoretical foundation nor clear-cut empirical base on FDI determinants, amidst the proliferation of FTAs associated with the overlapping tendencies (‘spaghetti bowl’), stalled Doha Development Multilateral negotiation, and the increasing argument on whether such FTAs can stimulate sustainable growth through, amongst other factors FDI (Yeats, Amjadi, Reincke, & Ng, 1997). This study examines whether the Free Trade Area (FTA) of the Common Market for Eastern and Southern Africa (COMESA) can predict the inward Foreign Direct Investment (FDI). Considering the limitation on the benchmark test (OLS Fixed Effect), the Feasible Generalized Least Squares (FGLS) robustness exhibits a positive and strong influence of COMESA-FTA on inward FDI. However, the interactive magnitudes of the FTA with Institutional Quality (IQ) and Financial Development Index (FINDI) demonstrate an inverted-U negative and significant relationship with inward FDI. Trade Openness (TOP) and the Human Development Index (HDI) have positive associations with the inward FDI, while FINDI adversely affected inward FDI. The findings suggest that FTA, TOP, HDI, and FINDI should be considered in policy. harmonization and implementation. However, the mixed coefficients of FTA across models singling unnecessary administrative burdens and inconducive policies that may create barriers from attracting FDI.